Characterisation and expression analyses of two putative cerato-platanin proteins isolated from Ganoderma boninense Pat. - Hamid, Sathyapriya; Chai, Ling Ho; Abdullah, Siti Nor Akmar; Ti, Eng Leslie Low; Nagappan, Jayanthi; Mui, Yun Wong (Academic Press, 2024)
Cerato-platanin (CP) proteins are small extracellular proteins that play essential roles in the plant-pathogen interactions of some economically important filamentous fungi. At present, there is a lack of information about the roles of CP proteins secreted by Ganoderma boninense, the causal agent of basal stem rot disease in African oil palm, during the early host-pathogen interaction. This work studies the properties and roles of two CP proteins from G. boninense strain PER71. Using bioassay-guided fractionation and nano-LC-MS/MS analysis, we identified peptide matches for G. sinense ZZ0214-1 CP-like and other elicitor proteins in the culture filtrate of G. boninense strain PER71. We found that GbCP2 and GbCP6, two out of nine CP gene models identified in the fungal genome of G. boninense strain PER71, exhibited potential effector properties. We further validated their effector properties by isolating and characterising their coding regions. Interestingly, GbCP6 showed a significant expression level at 11 days post inoculation, indicating its significance in fungal pathogenesis. On the other hand, GbCP2 did not show differential expression at any sampling point, suggesting a different function or role in the pathogenicity of G. boninense. This study identifies GbCP6 as a potential biomarker for early detection of basal stem rot disease in oil palm.